Corrosion and Electrical Properties of SS316L Materials in the Simulated HT-PEFC Environment. Issue 10 (1st January 2018) - Li, Ruiyu; Cai, Yun; Wippermann, Klaus; Lehnert, Werner
Abstract : Increasing attention is being paid to the use of metallic materials as a replacement for non-porous graphite in the bipolar plates of polymer membrane fuel cells, including high-temperature polymer membrane fuel cells (HT-PEFCs). This work investigates the corrosion and electrical properties of SS316L stainless steel in the simulated anode and cathode environments of HT-PEFCs. The influence of gases on the free corrosion potential (Ecorr ), free corrosion current (icorr ) and dynamic formation of passive layers were analyzed in 85 wt% phosphoric acid at RT and 130°C by means of potentiodynamic and potentiostatic tests, together with open circuit potential (OCP) measurements. The working potential of the anode (0.05V) is located in the active corrosion region, while the working potential of the cathode (0.65V) is located in the passive corrosion region. The potentiostatic tests show that the corrosion rate of SS316L in the simulated anode environment of an HT-PEFC is 10 times higher than that in the simulated cathode environment of an HT-PEFC. The free corrosion potentials, immediately noted after potentiostatic tests, show that the existence of oxygen could improve the stability of the passive layer formed during the potentiostatic stage. Scanning electron microscopy (SEM) results showed different morphologies of the corroded surface. Inductively-coupled plasma optical emission spectrometry (ICP-OES) and interfacial contact resistance (ICR) was then used to determine the levels of metal ions in the solution after corrosion and the influence of the passive layer on the ICR of metallic bipolar-plates separately made from SS316L. X-ray photoelectron spectroscopy (XPS) was used to investigate the distribution of elements on the surface of samples before and after the corrosion tests. These ex-situ measurements showed that in the anode environment, SS316L undergoes active corrosion, which results in a higher level of leaching metal ions and lower value of ICR compared to that in a cathode environment, which has a passive corrosion environment. The specimen in the cathode environment showed lower values of ICR and the number of leaching metal ions when exposed to oxygen compared with the nitrogen atmosphere. The passive layer formed in a simulated cathode environment with an oxygen purge shows the best corrosion resistance within hot phosphoric acid. The XPS results indicate that this is a Cr-rich layer. The thickness of the surface films was estimated to range from 1.1–2.2 nm.